Intergenerational crosstalk of brain-gut axis in parental Nd2O3 exposure-induced offspring neurotoxicity and cognitive dysfunction: a mechanistic study - Jia, Yujing; Cao, Jing; Guo, Yan; Wu, Lihong; Du, Xiaoyan; Tang, Bofu; Xia, Bingtao; Deng, Yang (Frontiers in Public Health, 2024)
IntroductionRare earth elements (REEs) are widely used in plenty of fields. REEs have significant neurotoxicity and it may adversely affect the development of cognitive. For example, neodymium will causing neurological damage through penetrate the blood–brain barrier (BBB). However, whether it disrupts the balance of brain-gut axis (BGA) crosstalk and affects the intestinal microecology disorder of host is still unclear. This study investigated the neural damage on children caused by maternal exposure to Neodymium oxide (Nd2O3) during pregnancy, and its involved mechanism of BGA injury.MethodsWe used rat model to investigated the mechanisms of the offspring’s neural damage that Nd2O3 exposure in pregnancy. To verify the neural damage of offspring rats, we examed BBB-related factors, such like glutamate and ROS levels in brain tissue, behavioral tests, hippocampal and cortical damage, as well as changes in gut microbiota, intestinal mucosal barrier, and SCFAs in the intestine. Also, we observed some specific indicators of intestinal immune barrier function and gut nerve-related indicators.ResultsMaternal Nd2O3 exposure reduced the content of offspring tight junction proteins, increased BBB permeability, leading to Nd accumulation and brain tissue inflammation, affecting offspring’s neural development and weakening their spatial learning ability. Nd2O3 also disrupted BBB integrity by regulating SCFAs and BGA. Probiotic intervention in the offspring rats exposed to 2% Nd2O3 showed significant recovery of inflammation in both brain and colon tissues, and reduced BBB permeability.ConclusionMaternal exposure to Nd2O3 affects the offspring’s BGA, targeting brain and colon tissues, increasing BBB permeability, affecting neural development, causing damage to the intestinal mucosa, and impacting children’s gut development. Probiotics can alleviate these effects. These findings provide valuable insights into understanding the neurodevelopmental and intestinal developmental toxicity of Nd2O3 and its prevention and treatment. It also calls for a comprehensive assessment of the health risks of susceptible populations to Nd2O3, such as pregnant women. It may providing theoretical basis for preventing and controlling neodymium-induced harm in children by examing the repair mechanism of the damage through probiotic intervention.